The Development of Modern Indonesian Islamic Theology and Sufism in the Environment of Al-Jam'Iyatul Washliyah - Komaruddin, Didin; Ismail , Ecep (Syifa al-Qulub : Jurnal Studi Psikoterapi Sufistik, 2024)
Al Jam'iyatul Washliyah is an Islamic organization founded in North Sumatra in 1930. The main focus of this organization is on Islamic education and preaching, as well as efforts to integrate Islamic teachings with nationalist values. This research uses a qualitative approach based on literature study, by examining relevant texts and literature. Research findings show that Al Jam'iyatul Washliyah seeks to align Islamic teachings with contemporary issues such as education, health and welfare. Theological and sufisme thinking in this organization reflects a response to the challenges of modernity and has made significant contributions to education and preaching, as well as promoting tolerance and moderation in a diverse society.